2001
DOI: 10.1177/1524838001002003004
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment of Denial, Cognitive Distortions, and Victim Empathy among Pedophilic Sex Offenders

Abstract: The modification of denial, defensiveness, and cognitive distortions and the enhancement of victim empathy are central components in the treatment of pedophilic sex offenders (PSOs) and are thus important factors to evaluate. This review of the literature highlights three broad problems with self-report measures of these variables. First, the psychometric properties of measures vary enormously, with some having no established validity or reliability. Second, the purpose of the measure is generally quite transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…More broadly, it could be argued that many of the self-report measures used to assess empathy do not directly measure the respondent's ability to be empathetic, but instead measure the respondent's understanding of the construct: for example, the Perspective Taking subscale of the IRI 3 appears to measure the respondent's assessment of the extent to which they habitually consider the perspectives of other people rather than their actual perspectivetaking ability (Hanson & Scott, 1995). It has also been suggested that the transparent nature of self-report empathy measures may leave them open to the influence of social desirability on responding when assessing sex offenders (Tierney & McCabe, 2001; for specific analysis of the IRI see Curwen, 2003). Researchers can control for this by using empathy measures that assess socially desirable responding or by using additional measures to identify such responding; however, nearly half of the studies that used self-report tools did not describe attempts to control for social desirability (Burke, 2001;Hunter & Figueredo, 2000;Moriarty et al, 2001;Netland & Miner, 2012;Lindsey et al, 2001;Van Vugt et al, 2008).…”
Section: Assessment Toolsmentioning
confidence: 99%
“…More broadly, it could be argued that many of the self-report measures used to assess empathy do not directly measure the respondent's ability to be empathetic, but instead measure the respondent's understanding of the construct: for example, the Perspective Taking subscale of the IRI 3 appears to measure the respondent's assessment of the extent to which they habitually consider the perspectives of other people rather than their actual perspectivetaking ability (Hanson & Scott, 1995). It has also been suggested that the transparent nature of self-report empathy measures may leave them open to the influence of social desirability on responding when assessing sex offenders (Tierney & McCabe, 2001; for specific analysis of the IRI see Curwen, 2003). Researchers can control for this by using empathy measures that assess socially desirable responding or by using additional measures to identify such responding; however, nearly half of the studies that used self-report tools did not describe attempts to control for social desirability (Burke, 2001;Hunter & Figueredo, 2000;Moriarty et al, 2001;Netland & Miner, 2012;Lindsey et al, 2001;Van Vugt et al, 2008).…”
Section: Assessment Toolsmentioning
confidence: 99%
“…The influence of social desirability on responding was also evaluated, as this is considered to be a particular problem in the assessment of sex offenders (McGrath, Cann, & Konopasky, 1998;Stermac, Segal, & Gillis, 1990;Tierney & McCabe, 2001b).…”
Section: Studymentioning
confidence: 99%
“…For example, Tierney and McCabe (2001) found a correlation of r ¼ .01 between the Empathy Scale-Child which measures empathy towards victims of child sexual abuse, and the Empathy Scale-General, measuring global empathy and a correlation of r ¼ .13 between the Empathy Scale (Child) and the Questionnaire Measure of Emotional Empathy in a community group sample of 40 males. They concluded that general empathy and victim empathy may be unrelated.…”
mentioning
confidence: 95%